Hush : Media and Sonic Self-Control - Hagood, Mack (Book collections on Project MUSE., 2019)
Mack Hagood outlines how noise-cancelling headphones, tinnitus maskers, white noise machines, nature-sound mobile apps, and other forms of media give users the ability to create sonic safe spaces for themselves, showing how the desire to block certain sounds are informed by ideologies of race, gender, and class.